A farmer group model to promote innovation uptake and market access in northwest Vietnam - Thinh, Nguyen Thi; Thanh, Lo Quang; Le, Pham Thi; Atieno, Mary; Burkart, Stefan (International Livestock Research Institute, 2024)
The Northwest Highlands of Vietnam (NWH) is characterized by a significant concentration of ethnic minority communities, elevated poverty rates, a high livestock density, and the crucial role that livestock plays in the local economy. Besides, the region faces several urgent environmental, market, and production challenges (CGIAR Research Program on Livestock, 2020). Within livestock species, pigs and beef cattle are recognized as crucial value chains, significantly contributing to the improvement of livelihoods and food security in the region. However, both value chains exhibit low productivity, attributed to inadequate animal husbandry practices, disease threats, parasites, and unsuitable technologies related to feed, breeds, and herd health. Additionally, poor coordination and connections among stakeholders lead to inefficiencies across the value chains and disparities in the benefits received from livestock-related innovations.